2002
DOI: 10.1002/jsfa.1162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of food dry matter intake on the flow of amino acids at the terminal ileum for rats fed an enzyme‐hydrolysed casein‐based diet

Abstract: The aim of the study was to determine whether food dry matter intake had an effect on endogenous ileal amino acid flows in the rat when the flows were expressed in units of mg g À1 dry matter. Eighty 200 g body weight rats were trained for 7 days to consume a casein-based diet over a daily 3 h feeding period, and then an enzyme-hydrolysed casein (MW < 5000 Da)-based diet, with chromic oxide as an indigestible marker, was fed for a further 8 days. The mean ratio of food intake to metabolic body weight over all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In contrast, the daily flow of IAA end increased as FI increased. This is in agreement with James et al (2002), who observed an increase in the daily loss of all AA with increasing DMI in rats. Similar results were also reported by Butts et al (1993) and Hess and Seve (1999).…”
Section: Endogenous Lossessupporting
confidence: 93%
“…In contrast, the daily flow of IAA end increased as FI increased. This is in agreement with James et al (2002), who observed an increase in the daily loss of all AA with increasing DMI in rats. Similar results were also reported by Butts et al (1993) and Hess and Seve (1999).…”
Section: Endogenous Lossessupporting
confidence: 93%
“…These observations appear to suggest that the endogenous AA flows, measured in relation to DM intake, may not be related to feed intake; further studies are needed to test this hypothesis. Published data on the effects of feed intake on endogenous AA flows in pigs have been contradictory (Butts et al 1993;Hess & Seve, 1999;James et al 2002). Studies by Angkanaporn et al (1997) have shown that the low feed intake in birds fed the GuC diet can be attributed to a direct effect of lysine deficiency and/or homoarginine per se on feed intake regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the mean feed intakes of the rats receiving the 200 g kg −1 zein diet were significantly greater than those for the rats receiving the other test diets. Dry matter intake has been shown to be linearly related to endogenous ileal amino acid flow 18, 19. Therefore, the endogenous ileal lysine flows determined in the present study were calculated on a dry matter intake basis, which would be expected to have accounted for the small differences in food intake between the rats receiving the different diets.…”
Section: Discussionmentioning
confidence: 94%